An Exploration for Future Mutual Research Partnership Between UNUSA And MANIPAL Globalnext University, Malaysia - Djuwari, Djuwari (Studies in Technology and Education, 2026)
This research article explores the potential mutual research partnership between Universitas Nahdlatul Ulama Surabaya (UNUSA) and Manipal GlobalNxt University Malaysia (MGUM). The primary objectives are to address societal challenges, foster academic exchange, and drive impactful solutions through interdisciplinary collaboration. Utilizing a qualitative research design, data were collected via open questions and informal discussions with key informants from both institutions as well as the participants. The research methodology involved the selection of key informants, development of open-ended questions, transcription of discussions, initial coding, theming, and data interpretation. The results indicate that the collaboration can significantly enhance educational quality, cross-cultural understanding, resource sharing, technological advancement, and strategic growth. However, challenges such as adaptation periods, technological disparities, and the need for strategic consensus were also identified. It can be concluded that the partnership between UNUSA and MGUM holds great potential for advancing education and research, provided that effective communication, flexible adaptation, capacity building, strategic planning, and sustainability are emphasized. The collaboration aims to harness the collective expertise of both institutions to generate tangible solutions for societal issues, thereby making meaningful contributions to global knowledge and development.